Conditions of the Water–Coal Fuel Drop Dispersion at Their Ignition in the Conditions of High-Temperature Heating; Combustion Science and Technology; Vol. 191, iss. 12 - Salomatov V. V. Vladimir Vasiljevich; Kuznetsov G. V. Geny Vladimirovich; Syrodoy S. V. Semen Vladimirovich; Gutareva N. Yu. Nadezhda Yurievna (2018, 2018)
Title screen